2021
DOI: 10.1007/s11748-021-01627-z
|View full text |Cite
|
Sign up to set email alerts
|

SMARCA4-deficient thoracic sarcoma revealed by metastasis to the small intestine: a diagnostic dilemma

Abstract: SMARCA4-deficient thoracic sarcoma (SMARCA4-DTS) is a recently identified aggressive subtype of sarcoma. We present the case of a 44-year-old man who underwent a surgery for a perforated small intestine. Compued tomography scan revealed a tissular mediastino–pulmonary mass.Histopathological examination of the intestinal mass shown a malignant tumour with a typical epithelioid and rhabdoid cells, numerous mitoses and large necrosis. A large panel of immunohistochemistry revealed loss of SMARCA4 and SMARCA2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Patients were strongly associated with smoking and were predominantly male, and our cases t these demographic characteristics. SMARCA4-UT is an aggressive tumor with a poor prognosis, often metastasizing to the lymph nodes, adrenal glands, brain, and so on [11][12] . The patient's symptoms are one of the most interesting aspects of this case and an important diagnostic challenge in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were strongly associated with smoking and were predominantly male, and our cases t these demographic characteristics. SMARCA4-UT is an aggressive tumor with a poor prognosis, often metastasizing to the lymph nodes, adrenal glands, brain, and so on [11][12] . The patient's symptoms are one of the most interesting aspects of this case and an important diagnostic challenge in the early stages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Leckey et al[ 26 ] found that p40 and p63 were rarely expressed in SMARCA4-UT. The immunohistochemical results of SMARCA4-UT are shown in Table 1 [ 5 , 9 , 14 , 15 , 17 , 23 26 , 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…When DNA is tightly packed, gene expression is inhibited. Moreover, SWI/SNF complexes recruit histone deacetylases (HDACs) to remove activated acetyl markers from histone tails, thereby inhibiting tumor cell cycle [ 28 , 32 , 35 ]. Not only that, part of the protein encoded by the mutated gene may be the regulatory factor of histone PTMs, tumor suppressor genes may be silenced by changes in PTMs level, and oncogenes may be activated by changes in PTMs level [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations